Gianpietro Mazzoleni e Anna Sfardini, Da “Porta a porta” a “L’isola dei famosi” (Altre Modernità, 2010)
Gianpietro Mazzoleni e Anna Sfardini, Da “Porta a porta” a “L’isola dei famosi”(Bologna, Il Mulino, 2009, pp. 181ISBN 978-88-15-13273-4)di Jole Morgante